KAJIAN POLA KETERKAITAN UMKM DAN INKLUSI KEUANGAN TERHADAP PENURUNAN ANGKA PENGANGGURAN DI INDONESIA - Nasution, Diwayana Putri (JURNAL ILMIAH EDUNOMIKA, 2024)
This study was conducted in Indonesia using data on variables related to SMEs (Small and Medium Enterprises), financial inclusion, and unemployment. The aim of the research is to understand and analyze the impact of SME variables and financial inclusion on reducing unemployment rates in Indonesia. SME variables considered include SME employment absorption, number of SMEs, SME investment, and SME income. The study uses 12 years of data from 2011 to 2022. Data were collected through documentation studies, which involve gathering and processing information from previous studies related to the research problem. The data used are quantitative, sourced from secondary time series data from the Central Statistics Agency (BPS), the World Bank, the Ministry of Cooperatives, and SMEs. Analytical methods employed include descriptive analysis and multiple linear regression, with data processing carried out using SPSS software. This research is expected to contribute to the understanding of the relationship between SMEs, financial inclusion, and unemployment during the COVID-19 pandemic. Descriptive analysis results indicate a pattern of correlation between SME variables and financial inclusion in reducing unemployment rates in Indonesia.